In Depth Breadth Analyses of Human Blockade Responses to Norovirus and Response to Vaccination - Joel Haynes; Virginia Perry; Evelyn Benson; Alisa Meeks; Gayle Watts; Heather Watkins; Ralph Braun (Viruses, 2019)
To evaluate and understand the efficacy of vaccine candidates, supportive immunological measures are needed. Critical attributes for a norovirus vaccine are the strength and breadth of antibody responses against the many different genotypes. In the absence of suitable neutralization assays to test samples from vaccine clinical trials, blockade assays offer a method that can measure functional antibodies specific for many of the different norovirus strains. This paper describes development and optimization of blockade assays for an extended panel of 20 different norovirus strains that can provide robust and reliable data needed for vaccine assessment. The blockade assays were used to test a panel of human clinical samples taken before and after vaccination with the Takeda TAK-214 norovirus vaccine. Great variability was evident in the repertoire of blocking antibody responses prevaccination and postvaccination among individuals. Following vaccination with TAK-214, blocking antibody levels were enhanced across a wide spectrum of different genotypes. The results indicate that adults may have multiple exposures to norovirus and that the magnitude and breadth of the complex preexisting antibody response can be boosted and expanded by vaccination.